Tissue-specific bioconcentration of antidepressants in fish exposed to effluent from a municipal sewage treatment plant - Grabicova, Katerina; Lindberg, Richard H; Ostman, Marcus; Grabic, Roman; Randak, Tomas; Larsson, D G Joakim; Fick, Jerker (The Science of the total environment, 2014)
Tissue-specific bioconcentration of selected antidepressants was studied in rainbow trout (Oncorhynchus mykiss) exposed to undiluted effluent from a Swedish municipal sewage treatment plant for 13 days. Citalopram, sertraline and venlafaxine were found in the brains and livers of most fish, but not in blood plasma or muscle. Venlafaxine was the only drug found in plasma (3/20 fish). Fluoxetine was not detected in any fish tissue, in accordance with a low concentration in the effluent and a comparably high limit of quantification in tissues. Concentrations of citalopram, sertraline and venlafaxine in fish brain were up to 1/12, 1/8 and 1/26, respectively, of the lowest concentrations found in the brains of mammals treated with therapeutic doses. Thus, given co-exposure to several antidepressants and an assumed similar potency in fish, the margin of safety for target-related effects in fish residing in effluent-dominated streams is relatively low. Furthermore, the non-detectable levels of these drugs in blood plasma suggest that analyses of concentrations in target tissues (brain) would be more informative in field studies and other studies with environmentally realistic exposure concentrations.
Keywords: Liver; Animals; odpad tekutý - odstraňování; Antidepressive Agents; Rainbow trout; chemické látky znečišťující vodu; Water Pollutants, Chemical; Sewage; Caged fish; monitorování životního prostředí; Waste Disposal, Fluid; Venlafaxine; Brain; Environmental Monitoring; Selective serotonin reuptake inhibitors; Oncorhynchus mykiss; zvířata; odpadní vody; antidepresiva